2018
DOI: 10.4172/2150-3508.1000242
|View full text |Cite
|
Sign up to set email alerts
|

Helminthiasis and Gram Negative Enteric Bacteria in Freshwater Fish from Selected Lakes of Haramaya District, Ethiopia

Abstract: Microbiological and helminthiasis examination of fish from Tinike and Adelle Lakes were conducted at Haramaya District, Ethiopia. The types of fish available in the lakes were also assessed. Adelle Lake has only Clarias gariepinus while the Tinike Lake has only Oreochromis niloticus fish species. Ten fish of each species, 20 in total, were collected from the lakes and post-mortem examined for the presence of adult helminthiasis in the body parts. Twelve samples from different body parts of each fish, 240 sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
(23 reference statements)
1
9
1
Order By: Relevance
“…For tetracycline, 55.6%, 8.3% and 36.1% of the isolates were resistant, intermediate and susceptible, respectively. Much research indicates that E. coli is not responding to tetracycline treatment, 45 , 46 which corresponds to the results of the current study. However, Mohammed et al 47 showed that Escherichia coli was susceptible to tetracycline.…”
Section: Discussionsupporting
confidence: 87%
“…For tetracycline, 55.6%, 8.3% and 36.1% of the isolates were resistant, intermediate and susceptible, respectively. Much research indicates that E. coli is not responding to tetracycline treatment, 45 , 46 which corresponds to the results of the current study. However, Mohammed et al 47 showed that Escherichia coli was susceptible to tetracycline.…”
Section: Discussionsupporting
confidence: 87%
“…Edwardsiella infection in sh usually occurs under imbalanced environmental conditions such as high water temperature, poor water quality, and high organic content (Tesfaye et al, 2018). However, in contrary there was no report of the occurrence of E. tarda according to study conducted at selected Lake Adelle and Tinike of Haramaya District, Ethiopia in the study of helminthiasis and gram negative enteric bacteria in freshwater sh (Hiko et al, 2018).…”
Section: Results Based On Sh Speciesmentioning
confidence: 99%
“…Salmonella sp. has been isolated at the farm level from tilapias [ 130 , 261 , 285 ] and African sharp-tooth catfish [ 63 ], in retail catfish/other cultured freshwater fish [ 59 , 262 , 286 ] and in an array of imported seafood [ 60 , 287 , 288 , 289 , 290 , 291 ]. In the USA, the incidence of Salmonella contamination in imported raw fish was 12.2%, with Vietnam having the highest by country basis [ 60 ].…”
Section: Discussionmentioning
confidence: 99%